2015
DOI: 10.1186/s12889-015-2474-y
|View full text |Cite
|
Sign up to set email alerts
|

Being lonely or using substances with friends? A cross-sectional study of Hungarian adolescents’ health risk behaviours

Abstract: BackgroundStudying adolescents’ health risk behaviours is oddly significant in Central and Eastern European countries, where the prevalence of smoking and drinking among 14–18 year old students is significantly high. The goal of our study is to examine the role of social psychological and social behavioural variables in health risk behaviours among Hungarian adolescents.MethodsOur sample was comprised of three high schools of Debrecen (the second largest city of Hungary). In all, 501 students filled in the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
2
13
1
1
Order By: Relevance
“…These results are consistent with other studies in which having drug using family members and friends increased the risk of health-risk behaviors among adolescents [ 41 , 42 ]. Similarly, other studies have found that smoking and alcohol use by friends increased the risk of alcohol use and other health-risk behaviors by the adolescents [ 43 , 44 ] while perceived peer norms on drug use were influential on alcohol and cannabis use among early adolescents [ 45 ]. This suggests that adolescent health-risk behaviors can be conceptualized as a result of both peer influence and selection processes, with peer influences enhancing risk-taking among adolescents [ 46 ] and adolescents selecting friends who engage in similar levels of risk behaviors.…”
Section: Discussionmentioning
confidence: 77%
“…These results are consistent with other studies in which having drug using family members and friends increased the risk of health-risk behaviors among adolescents [ 41 , 42 ]. Similarly, other studies have found that smoking and alcohol use by friends increased the risk of alcohol use and other health-risk behaviors by the adolescents [ 43 , 44 ] while perceived peer norms on drug use were influential on alcohol and cannabis use among early adolescents [ 45 ]. This suggests that adolescent health-risk behaviors can be conceptualized as a result of both peer influence and selection processes, with peer influences enhancing risk-taking among adolescents [ 46 ] and adolescents selecting friends who engage in similar levels of risk behaviors.…”
Section: Discussionmentioning
confidence: 77%
“…All the scales and questionnaire items were translated into Hungarian and back translated by bilingual translators, and the majority of them have been applied and adapted to Hungarian adolescent populations in previous studies (Piko et al, 2005;Varga & Piko, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Across a range of populations and study types, conflicting evidence on the relationship between loneliness and alcohol consumption has been presented. Some correlational studies in College students ( McBroom, Fife, & Nelson, 2008 ), and adolescents ( Varga & Piko, 2015 ), have shown an inverse relationship between loneliness and alcohol use; whereas others have provided a positive correlation between the two in adult ( Bonin, McCreary, & Sadava, 2000 ), student ( Cacioppo, Hawkley, Crawford, et al, 2002 ), and adolescent ( Barbosa Filho et al, 2012 , Carvalho et al, 2011 ) populations.…”
Section: Introductionmentioning
confidence: 99%